A transdiagnostic examination of affective motivations for drug use - Miglin, Rickie (Addict Behav Rep, 2020)
INTRODUCTION: Substance use often co-occurs with both internalizing and externalizing disorders, highlighting the importance of understanding reciprocal relations among problematic drug use and psychopathology. We examined affective (approach and avoidance) motivations for drug use as potential transdiagnostic constructs that relate to symptoms of common clinical disorders. METHODS: 175 community adults with a lifetime history of drug use reported on their motivations for use, frequency of use, and DSM-5 lifetime psychopathology symptoms. Linear regression was used to examine associations between drug use motivations and psychopathology. RESULTS: Avoidance motivations for drug use (e.g., using to cope with distress) correlated positively with symptoms of both internalizing and externalizing disorders, borderline personality disorder, and psychiatric comorbidity. In contrast, approach motivations for drug use (e.g., using to get a thrill) correlated only with substance use disorder symptoms. Notably, motivations for drug use continued to show these transdiagnostic associations after accounting for general approach-avoidance motivational tendencies. CONCLUSION: These findings suggest that affective motivations for drug use provide a useful framework for conceptualizing substance problems that cuts across traditional dimensions of psychopathology.